Single-cell trajectory analysis of human homogenous neurons carrying a rare RELN variant - Arioka, Yuko (Transl Psychiatry, 2018)
Reelin is a protein encoded by the RELN gene that controls neuronal migration in the developing brain. Human genetic studies suggest that rare RELN variants confer susceptibility to mental disorders such as schizophrenia. However, it remains unknown what effects rare RELN variants have on human neuronal cells. To this end, the analysis of human neuronal dynamics at the single-cell level is necessary. In this study, we generated human-induced pluripotent stem cells carrying a rare RELN variant (RELN-del) using targeted genome editing; cells were further differentiated into highly homogeneous dopaminergic neurons. Our results indicated that RELN-del triggered an impaired reelin signal and decreased the expression levels of genes relevant for cell movement in human neurons. Single-cell trajectory analysis revealed that control neurons possessed directional migration even in vitro, while RELN-del neurons demonstrated a wandering type of migration. We further confirmed these phenotypes in neurons derived from a patient carrying the congenital RELN-del. To our knowledge, this is the first report of the biological significance of a rare RELN variant in human neurons based on individual neuron dynamics. Collectively, our approach should be useful for studying reelin function and evaluating mental disorder susceptibility, focusing on individual human neuronal migration.